(3YGOGJ GdbQBf GdCSdhHjI (B:s (3OQGSI JWHjbjI (B/s - (3GdKfjGf, QGTO Hf MehO Hf QGTOs ((3GdQjGV (B:s (3OGQ GdJOeQjI,s, 2012)
(3jJfGhd cJGH (B((3YGOGJ GdbQBf GdCSdhHjI OQGSI JWHjbjI(B) (3hGdPj bGe HJCdjag O(B. (3QGTO Hf MehO Hf QGTO GdKfjGf, ehVhY (B((3GdbQBf(B) (3GdcJGH OQGSI YGOGJ GdbQGf aj GdCSGdjH GdYQHjI, eKd cja heJi jcQQ hdG jcQQ, eJi jMOK heJi jVeQ, hGdEXgGQ, hGdVejQ GdZGFH hGdeNGWH, hGdMQha hCfhGYgG, hEHOGd MQa HMQa heJi jchf(B. (3hgj ef GdCTjGA GdeajOI aj JQLjM CbhGd GdJaSjQ, hJbY aj aUdjf Chdge aj CKQ gPg GdYGOGJ aj GdbQGAGJ, haUd BNQ aj CKQgG Ydi GdJaSjQ(B. s
(3GdCUd CWQhMI (B((3OcJhQGg(B) s
(3HHdjhLQGajI (B: (3UaMI (B677-698.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1-2.s
Keywords: (3GdbQBfs -- (3dZI, CSdhHs; (3GdbQBfs -- (3CdaGXs; (3GdbQBfs -- (3HdGZIs; (3GdbQBfs -- (3CdaGXs